EVALUATION OF MECHANICAL PROPERTIES OF Al-SiC METAL MATRIX COMPOSITES SYNTHESIZED BY STIR CASTING METHOD - A., S. HARI VIJAY; K. , SHANMUGANANTHAM; S. , SURESH KUMAR (International Journal of Psychosocial Rehabilitation, 2020)
On account of the excellent physical and mechanical properties of composite materials, they are widely used in many engineering applications, such as in tank armor and automotive disc brakes. Metal-matrix composites are a relatively new range of materials possessing several characteristics that make them useful in situations where low weight, high strength, high stiffness, and an ability to operate at elevated temperatures are required. Despite the superior mechanical and thermal properties of metal-matrix composites, their poor machinability has been the main cause of their substitution for metal parts. The hard abrasive reinforcement causes rapid tool wear during machining and, consequently, high machining costs. In this work, an attempt is made to fabricate an Al/SiC metal matrix composite with a 6.6% weight fraction constituted by SiC particles, and the machinability of the fabricated specimen is evaluated by a micro-drilling process on a CNC vertical machining center using an 800μm diameter tungsten carbide tool. The design and optimization of the experiment are implemented with the help of the full factorial method. The holes are then analyzed to evaluate their surface integrity, including taper and burr formations.